Medical assistance in dying (MAiD): Canadian nurses’ experiences - Beuthin, Rosanne (Nurs Forum, 2018)
Medical assistance in dying (MAiD) represents a historic change in Canadian society and the provision of end‐of‐life care. In this descriptive narrative inquiry, 17 nurses were interviewed during the first 6 months of assisted dying becoming a legal option for patients in Canada. Nurses’ experiences of either providing care for a patient who had chosen MAiD, or declining to participate in MAiD, were explored. Findings describe three themes and eight storylines of the impact of MAiD on nurses’ view of the profession, clinical practice, and personally. While most nurses perceived MAiD as an extension of the profession and their nursing practice, a small number also expressed moral distress as they grappled with assisted dying. Narratives illustrated an ongoing sensemaking process and spectrum of emotions. These findings offer insight and provide direction for nurses and managers in this new clinical and legal reality. Further research is needed to understand more fully the moral distress of some nurses, as well as the importance of communicating openly and nonjudgmentally with patients, families, and the health‐care team.